The Threshold Level of Fiscal Policy Instruments that can Promote Economic Development in Mexico, Indonesia, Nigeria and Turkey (British Journal of Multidisciplinary and Advanced Studies, 2025)
The paper determined the threshold level of fiscal policy instruments that can promote economic development in the MINT countries between 1981 and 2022 by the use of Dynamic Ordinary Least Squares (DOLS) technique to derive the estimates for threshold values of fiscal instruments. It was revealed that the MINT countries exhibit symmetric relationship between government expenditure and unemployment, with positive shocks stimulating economic activity and negative shocks decreasing unemployment. The results also exhibited asymmetric relationship between fiscal variables and poverty rates as shocks to government expenditure, government revenue and public debt confer both positive and negative non-linear impact on poverty levels on these countries. Policymakers across the MINT countries should prioritize spending on programmes directly impacting poverty reduction, unemployment reduction and improving the well-being of the citizens.